IMPLEMENTASI PROGRAM COOPERATION SECURITY INITIATIVE SEBAGAI UPAYA AS DAN NIGERIA DALAM MENEKAN DISTRIBUSI NARKOBA NIGERIA MENUJU AS TAHUN 2009-2013 - Bella, Elsa Nataya (Global and Policy Journal of International Relations, 2019)
The study aims to illustrate the cooperation undertaken by the Governments of the United States and Nigeria in the war against drugs through a non-military solution that focuses on non-military efforts. Non-military efforts have been taken by the U.S. by coordinating together until the establishment of a program applied in accordance with some scope of cooperation applied in non-military efforts applied in the case of drug trafficking in Nigeria is the establishment of the Cooperation Security Initiative program which formed and implemented several programs in the form of Fund assistance and technical assistance, Narcotics and Controlled Substances Strategy (NCS), Nigerian Epidemiological Network on Drug Use (NENDU), Police Initiative and AIRCOP, Maritime and Airport Security Assistance, joint Security coordination through Detection, Monitoring and Interdiction Operations, License Plate Rider and law enforcement training. The Program started to apply the U.S. and Nigeria in 2009- 2013. The Cooperation security Initiative Program ended in 2013 due to a decrease in drug smuggling from Nigeria to the US and agreed to an extradition treaty in the Drug Trafficking Act of 2013. Keywords: Transnational Crime, Drug Trafficking, Bilateral Cooperation, Cooperation Security Initiative DOI : https://doi.org/10.33005/jgp.v7i01.1815